Calculation of pH Values for Mixed Waters - Qian Hui; Song Xiuling; Zhang Xuedi; Yang Chao; Li Peiyue (E-Journal of Chemistry)
Mixing of waters with different compositions is a common phenomenon. The pH of mixed water can be calculated by introducing charge neutrality equation into the equations for equilibrium distribution calculation of species in water. In this paper, the equations thus obtained were solved by golden section method. To verify the calculation method, laboratory experiments were done for three sets of mixing water. The results showed the calculated pH values are in good agreement with measured ones.